2019
DOI: 10.1541/ieejjia.8.652
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Control Method for LLC Converter Utilized for Input-Parallel-Output-Series Inverter System with Solid-State Transformers

Abstract: A multi-level power converter with series-connected solid-state transformer (SST) units for a power conditioning system for photovoltaic (PV) generation was developed. Each SST unit has an LLC converter driven by SiC-MOSFETs and a high-frequency transformer. By applying the developed converter, the system can be optimized and made lighter than a conventional system using a commercial transformer. A method for controlling the LLC converter so as to maintain its high efficiency over a wide voltage range of a PV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In the AVS method, when σp = 4, the calculation of the maximum power for a module Pmax_σp4 is the same as (8). The calculation of the minimum power for a module Pmin_σp4 is same as (9).…”
Section: Stable Operation Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the AVS method, when σp = 4, the calculation of the maximum power for a module Pmax_σp4 is the same as (8). The calculation of the minimum power for a module Pmin_σp4 is same as (9).…”
Section: Stable Operation Regionmentioning
confidence: 99%
“…Considering in high power traction PET, a CHBR with 11 or more H-Bridge modules is necessary [31], which means the switching loss of CPS-PWM will be significantly higher than the AVS method. Many other studies [4,[8][9][10]12] have also shown a high sensitivity to switching losses and efficiency. Taking into account the three more important factors: SOR (voltage balance capacity), input current (stabilty and efficiency of power system) and switching loss (efficiency), the AVS method is a better one among the four methods.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The LLC converter is expected to eliminate the switching loss by the soft switching feature of the LLC converter, and the input‐series output‐parallel configuration is suitable for high power and downsized design for the isolated DC–DC converter. This circuit configuration is used in different applications with a particular control . The DC link voltage in the secondary side of the transformer is controlled to keep the DC 1.5 kV constant.…”
Section: Power Electronics Solutions For Rolling Stockmentioning
confidence: 99%
“…However, in a system in which a DC bus including an NPC inverter with an AC voltage controller is divided by a series capacitor, since it is difficult to adjust the voltage balance of the series capacitor via an AC terminal, a balance circuit is required. In addition, as a system for interconnection with a 6.6 kV power grid system, a converter technology using an extended system in which an inverter and an insulated converter are combined as a set has been reported (1)- (3) . In these studies, to serialize one end of the unitized converter to generate a high voltage, the other end must be connected to a DC voltage source.…”
Section: Introductionmentioning
confidence: 99%